PKM INTRODUKSI ALAT TANGKAP BUBU PAYUNG UNTUK MENINGKATKAN PENDAPATAN NELAYAN DI PERAIRAN DESA TAMANGAPA KECAMATAN MA’RANG KABUPATEN PANGKEP - Tajuddin, Mustamin; Ihsan, Ihsan; Tang, Beddu (JURNAL PENGABDIAN MASYARAKAT KAUNIAH, 2023)
Ecologically, the habitat of aquatic ecosystems and their reef fish, such as crabs and shrimps and other species is the most important area as a link in the chain of aquatic productivity in the sea.Umbrella holder is one of the fishing gear that will be introduced to partner fishermen groups is expected to increase the productivity of fishermen's catches. The Purpose of PKM is to Increase Income and Living Standards of Fishermen in the Waters of Tamangapa Village, Ma'rang District, Pangkep Regency. This PKM will be held for approximately 3 months from September to November 2022 in Tamangapa Village, Ma'rang District, Pangkep Regency. The technology of environmentally friendly bubu umbrella fishing gear to increase the income and living standards of fishermen in Tamangapa Village, Ma District, rang Pangkep Regency, in the management of fishing and non-fish businesses, is responded well by fishermen and improves fishermen's knowledge and skills. Increasing the knowledge and skills of partner fishermen groups in Tamangapa Village, Ma'rang District, Pangkep Regency in managing the business that has been carried out so far, so that the fishing business carried out so far productivity has increased so that the business can develop wel